2004
DOI: 10.1097/01.jom.0000105912.29242.5b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coexposure to Noise and Mixture of Organic Solvents on Hearing in Dockyard Workers

Abstract: Questionnaire and audiometric data of 701 dockyard workers (517 noise and organic solvent mixture-exposed and 184 noise-only-exposed) were referred to 205 control subjects not exposed to either noise or solvents. The odds ratio (OR) of hearing loss was significantly increased by approximately 3 times in the noise-only group and by almost 5 times in the noise and solvent group. A moderate effect of solvent ototoxicity, in addition to noise, was observed on hearing threshold at a frequency 8 kHz. ORs for hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 20 publications
3
64
0
8
Order By: Relevance
“…In the study by M. Śliwińska-Kowalska et al, multiple linear regression analysis revealed a correlation between exposure to solvent mixture (expressed as a lifetime exposure index) and hearing threshold at 8 kHz in dockyard workers [5]. The same authors have demonstrated a similar relationship for 4, 6 and 8 kHz, when the analysis concerned dockyard and paint & lacquer industry workers (high and moderate solvent exposure, respectively) [9].…”
Section: Hearing Acuity (Threshold)mentioning
confidence: 51%
See 4 more Smart Citations
“…In the study by M. Śliwińska-Kowalska et al, multiple linear regression analysis revealed a correlation between exposure to solvent mixture (expressed as a lifetime exposure index) and hearing threshold at 8 kHz in dockyard workers [5]. The same authors have demonstrated a similar relationship for 4, 6 and 8 kHz, when the analysis concerned dockyard and paint & lacquer industry workers (high and moderate solvent exposure, respectively) [9].…”
Section: Hearing Acuity (Threshold)mentioning
confidence: 51%
“…The mean lifetime exposure (exposure level × duration of employment) to toluene ranged from 31-203 ppm, to xylene from 84 to 696 ppm, and exposure index from 10 to 67 [4,5]. The highest-level exposure was encountered in a dockyard [5], and the lowest levels were found in aviation and Fig. 1.…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 3 more Smart Citations